2002
DOI: 10.1021/jo016293b
|View full text |Cite
|
Sign up to set email alerts
|

(1Z,3Z)-1,4-Di(pyridin-2-yl)buta-1,3-diene-2,3-diol:  The Planar Highly Conjugated Symmetrical Enediol with Multiple Intramolecular Hydrogen Bonds

Abstract: 1H, (13)C, and (15)N NMR spectral data show that in chloroform solution (1Z,3Z)-1,4-di(pyridin-2-yl)buta-1,3-diene-2,3-diol, OO, is in ca. 9:1 equilibrium with (3Z)-3-hydroxy-1,4-di(pyridin-2-yl)but-3-en-2-one, OK, while no 1,4-di(pyridin-2-yl)-2,3-butanedione, KK, was detected. The species present in the tautomeric mixture were identified by comparing their experimental chemical shifts with those known for similar compounds as well as with the theoretically calculated (GIAO-HF/DFT) values. Ab initio calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 37 publications
(50 reference statements)
3
30
0
Order By: Relevance
“…Comparison of their energies (Table 1) shows that only OEa and OOa are expected to be present in the tautomeric mixture in vacuum. These results are in agreement with our earlier studies that show that the respective dienol and enol/ enaminone forms are more stable than 1,4-bis(pyridin-2-yl)butane-2,3-dione and 1,4-bis(quinolin-2-yl)butane-2,3-dione, respectively [6,7]. Solvent, especially this more polar and of more basic properties (DMSO) disfavors the enolimine tautomers.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Comparison of their energies (Table 1) shows that only OEa and OOa are expected to be present in the tautomeric mixture in vacuum. These results are in agreement with our earlier studies that show that the respective dienol and enol/ enaminone forms are more stable than 1,4-bis(pyridin-2-yl)butane-2,3-dione and 1,4-bis(quinolin-2-yl)butane-2,3-dione, respectively [6,7]. Solvent, especially this more polar and of more basic properties (DMSO) disfavors the enolimine tautomers.…”
Section: Resultssupporting
confidence: 93%
“…Their formulas as well as numbering of heavy atoms in the molecule can be seen in Scheme 1. Except some exceptionally unstable rotamers [6,7], other species of this type are also included there.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two compounds are isoelectronic. Recently [7] we found that proton transfer takes place in 1,4-di(pyridin-2-yl)butane-2,3-dione and that the highly conjugated dienol, (1Z,3Z)-1,4-di(pyridin-2-yl)buta-1,3-diene-2,3-diol, predominates over other tautomeric forms in chloroform. This tautomer is additionally stabilized by two strong intramolecular hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…It is the only form present in the crystal. [7] Knowing that benzoannulation may affect the tautomeric equilibrium both qualitatively and quantitatively, [8±14] we were very much interested to discover how it affects the tautomeric preferences of 1,4-di(pyridin-2-yl)butane-2,3-dione. Its tautomers and rotamers are shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%